EMPOWERMENT OF GRADE I STUDENTS ON CLEAN AND HEALTHY LIVING BEHAVIOR BY WASHING HANDS AND BRUSHING TEETH PROPERLY AT MADRASAH IBTIDAIYAH 2 ALKHOIRIYYAH GARUT - Andhika Lungguh Perceka, Andhika Lungguh Perceka; Hasbi Taobah Ramdani, Hasbi Taobah Ramdani; Desy Syswianti, Desy Syswianti; N. Ai Erlinawati, N. Ai Erlinawati; Herlin Rusyani, Herlin Rusyani; Taufik Huda, Taufik Huda (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Some of the diseases suffered by school children include influenza, worms, abdominal pain and diarrhea. Diarrhea is one of the highest diseases suffered by children because they do not wash their hands with soap. the purpose of implementing community service activities to foster understanding for MI 2 students to have a healthy cleans living behavior by washing hands with soap and brushing teeth. The method used in this community service activity is to provide counseling on proper hand washing with soap through seven steps of good and correct washing dan brushing the teeth. Based on the analysis of the situation and the problems faced by partners, lecturers as implementers of community service programs and professionals from universities and assisted by students will provide a solution to overcome the difficulty of washing hands in finding solutions to problems The solution offered by the team proposing the service program is the Extension of Clean and Healthy Living Behavior (PHBS) Program Through Hand Washing Activities Using Soap in Early Childhood. As a result of this community service activity, students have understood the benefits of washing hands with soap and brushing teeth.